2011
DOI: 10.1017/s1743923x11000341
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Latino Gender Gap: Gender Attitudes across Sex, Borders, and Generations

Abstract: M any cultural stereotypes exist regarding the "modernity" of values possessed by Latino immigrants, particularly in reference to gender norms. Common perceptions about Latin machismo and marianismo (the idea that women should be pure and moral) do not paint a portrait of gender egalitarian dispositions. These assessments are upheld by neomodernization theorists who specifically identify gender attitudes as a critical element of modernity. In applying a revisedThe authors wish to thank three anonymous reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…They are thus expected to become more supportive of gender equality if the destination society has a more gender equal culture than the origin society (e.g. Bejarano, Manzano, and Montoya 2011;Bernhardt, Goldscheider, and Goldscheider 2007;Diehl, Koenig, and Ruckdeschel 2009;Norris and Inglehart 2012;Röder 2014;Teney 2009)-as has been illustrate above for the situation studied here.…”
Section: Assimilation or Alienation?mentioning
confidence: 75%
See 4 more Smart Citations
“…They are thus expected to become more supportive of gender equality if the destination society has a more gender equal culture than the origin society (e.g. Bejarano, Manzano, and Montoya 2011;Bernhardt, Goldscheider, and Goldscheider 2007;Diehl, Koenig, and Ruckdeschel 2009;Norris and Inglehart 2012;Röder 2014;Teney 2009)-as has been illustrate above for the situation studied here.…”
Section: Assimilation or Alienation?mentioning
confidence: 75%
“…The studies focusing on gender equality attitudes among immigrants have found comparable effects (e.g. Bejarano, Manzano, and Montoya 2011;Crul, Schneider, and Lelie 2013;Diehl, Koenig, and Ruckdeschel 2009;Leaper and Valin 1996;Read 2003).…”
Section: Background: Gender Equality Attitudesmentioning
confidence: 98%
See 3 more Smart Citations